Corrosion protection through naturally occurring films: new insights from iron carbonate - Ahmad,EA; Chang,H-Y; Al-Kindi,M; Joshi,GR; Cooper,K; Lindsay,R; Harrison,NM (ACS Applied Materials and Interfaces, 2019)
Despite intensive study over many years, the chemistry and physics of the atomic level mechanisms that govern corrosion are not fully understood. In particular, the occurrence and severity of highly localized metal degradation cannot currently be predicted and often cannot be rationalized in failure analysis. We report a first-principles model of the nature of protective iron carbonate films coupled with a detailed chemical and physical characterization of such a film in a carefully controlled environment. The fundamental building blocks of the protective film, siderite (FeCO3) crystallites, are found to be very sensitive to the growth environment. In iron-rich conditions, cylindrical crystallites form that are highly likely to be more susceptible to chemical attack and dissolution than the rhombohedral crystallites formed in iron-poor conditions. This suggests that local degradation of metal surfaces is influenced by structures that form during early growth and provides new avenues for the prevention, detection, and mitigation of carbon steel corrosion.